Membrane Bioreactor and Dynamic Membrane Bioreactor Performance Comparison under the Same Conditions - Veral, Mehmet Akif; Kızılet, Abdullah; Çınar, Özer (Osman SAĞDIÇ, 2020)
This study aims comparative evaluation of two different membrane modules, 0.45 µm and non-woven dynamic membrane, in AeMBR for synthetic wastewater treatment. Filtration performances of both membrane materials were compared under same operational conditions. Throughout the filtration process, 99% and 95% chemical oxygen demand (COD) removal efficiencies were achieved relying upon 0.45 µm and non-woven dynamic membrane, respectively. AeMBR was successfully operated at 10 LMH and no chemical cleaning was employed for 30 days. It was perfectly operated up to 15 LMH and then 20 LMH. The turbidity and trans-membrane pressure (TMP) of 0.45 µm was usually higher at the begging compared with the dynamic membrane despite membrane clogging rates were comparable. Capillary suction time (CST), soluble microbial product (SMP), extracellular polymeric substances (EPS), specific resistance to filterability (SRF), attenuated total reflectance fourier transformed-infrared spectroscopy (ATR FT-IR) and denaturing gradient gel electrophoresis (DGGE) analyzes were performed to understand the characterization of the cake deposited on membranes. 16S rDNA region shown significant result in terms of air/ambient temperature change. For both membrane modules, offline chemical cleaning employment with NaOCl and sulfuric acid, respectively, almost completely eliminated foulants and it was found that chemically washed membranes showed pressure close to that of the new membrane.

Bu çalışma, sentetik atık su arıtımı için aerobik membran biyoreaktörde (AeMBR), 0,45 µm ve dokuma olmayan membran olmak üzere iki farklı membran modülünün karşılaştırmalı değerlendirilmesini amaçlamaktadır. Her iki membran malzemesinin filtrasyon performansları aynı operasyonel şartlar altında karşılaştırılmıştır. Filtreleme işlemi boyunca, 0,45 µm ve dokuma olmayan membran olmak üzere sırasıyla %99 ve % 95 kimyasal oksijen ihtiyacı (KOİ) giderim verimleri elde edilmiştr. AeMBR, 10 LMH'de başarıyla işletilmiş ve 30 gün boyunca hiçbir şekilde kimyasal yıkama uygulanmamıştır. Reaktör, 15 LMH akıya kadar mükemmel bir şekilde işletilmi ve sonra 20 LMH’de işletime devam edilmiştir. 0.45 µm membranın bulanıklık ve trans-membran basıncı değerleri, dokuma olmayan membrana nispeten başlarda genellikle yüksek sonuçlar vermiştir. Membranlar üzerinde oluşan kek tabakasının karakteristik özelliklerini belirlemek üzere kapiler emme süresi (CST), çözünür mikrobiyal ürün (SMP), hücre dışı polimerik bileşenler (EPS), süzülmeye karşı spesifik direnç (SRF), fourier dönüşümlü kızılötesi spektroskopisi (FT-IR) ve denatüre gradyan jel elektroforezi (DGGE) aanalizleri yapılmıştır. 16S rDNA bölgesi, hava/ortam sıcaklığı değişikliği açısından önemli sonuç göstermiştir. Her iki membran modülü için, sırasıyla NaOCl ve sülfürik asit ile yapılan kimyasal temizleme istihdamı, neredeyse tamamen tıkanmaları ortadan kaldırmış ve kimyasal olarak yıkanmış membranların, yeni membranlarınkine yakın basınç gösterdiği bulunmuştur.
Membran Biyoreaktör ve Dinamik Membran Biyoreaktör Performansının Aynı Koşullarda Kıyaslanması
Keywords: Dynamic membrane bioreactor; Non-woven; 0.45 μm membrane; Biological treatment; COD removal; PES; Dinamik membran biyoreaktör; Dokuma olmayan; 0.45 μm membrane; Biyolojik arıtım; KOİ giderimi